Acute and chronic malnutrition and their predictors in children aged 0–5 years in São Tomé: a cross-sectional, population-based study. (November 2016) - Valente, A.; Silva, D.; Neves, E.; Almeida, F.; Cruz, J.L.; Dias, C.C.; da Costa-Pereira, A.; Caldas-Afonso, A.; Guerra, A.
Abstract: Objective: Undernutrition is an important cause of morbidity and mortality in infants and children worldwide. The aim of this study was to evaluate the nutritional status and their predictors in children from 0 to 5 years of age in São Tomé. Study design: A cross-sectional study was conducted in São Tomé Island. Methods: A total of 1285 individuals were enrolled between January and May 2011. Children were measured, and height for age (HAZ), weight for height (WHZ) and body mass index (BAZ) Z-score were computed. Global acute undernutrition is defined as weight for height <−1 Z-score (wasting < −2 Z-scores) and global chronic undernutrition as length/height for age <−1 Z-score (stunting < −2 Z-scores). Relevant information was collected from individual health bulletins, namely gestational age and birth weight, as well as weight at 6, 12, 18 and 24 months for all individual above these ages. Mothers were invited to answer a specific questionnaire. Results: A high percentage of global acute undernutrition (30.9% in <24 months and 21.9% in ≥24 months) and global chronic undernutrition (32.5% in <24 months and 41.1% in ≥24 months) was observed. Appropriate birth weight for gestational age (AGA) is significantly associated with lower odds for both acute (OR 0.485 [95% CI 0.299–0.785]) and chronic undernutrition (OR 0.427 [95% CI 0.270–0.675]) in children >12 months. Weight gain above 0.67 Z-score in the first semester of life was strongly related to lower odds for both acute (OR 0.109 [95% CI 0.040–0.291]) and chronic undernutrition (OR 0.379 [95% CI 0.187–0.770]) in children >12 months of age. Similarly, mother's education seems to protect against acute (>12 months: OR 0.448 [95% CI 0.244–0.825]; >24 months: OR 0.186 [95% CI 0.064–0.540]) and chronic undernutrition (>12 months: OR 0.389 [95% CI 0.232–0.653]; >24 months: OR 0.324 [95% CI 0.171–0.625]). All logistic regressions were adjusted for all children (gender, age, gestational age, birth weight, breastfeeding, begin consumption alcohol), mothers (age, height, body mass index, educational level, number of previous pregnancies, smoking during pregnancy, alcohol consumption during pregnancy) and household (number of siblings and persons at home) variables included in the protocol. Conclusions: Birth weight, nutritional status, and the mother's education and weight gain particularly in the first year of life were important factors protecting against undernutrition during infancy and childhood. These results emphasize the importance of women's nutrition and of adequate birth weight and particularly weight gain during the first year of life in order to prevent wasting and stunting in childhood. Highlights: The prevalence of global malnutrition in São Tomé children aged 0–60 months is high. Normal birth weight is associated with lower odds for global malnutrition. Higher maternal education is associated with lower odds for global malnutrition. Gaining weight in the first semester of life seems to reduce later global malnutrition.